Does investing in sound corporate governance pay? A South African study - N. Mans-Kemp; P. D. Erasmus; S. Viviers (South African Journal of Business Management, 2017)
Despite increased recognition of the importance of sound corporate governance practices in emerging markets, previous researchers reported inconclusive evidence on the association between corporate governance and financial performance. Authors that predominantly focused on board-related variables might, however, have failed to reflect the complex nature of corporate governance. The financial performance measures employed in the majority of previous studies also ignored the potential risk-reducing benefits that sound corporate governance could hold for emerging market firms. The purpose of this article was thus to investigate the relationship between a comprehensive measure of corporate governance and the risk-adjusted performance of selected South African companies. A unique corporate governance database was compiled by conducting content analysis on the considered companies' annual reports over the period 2002 to 2010. Aspects related to nine corporate governance categories were taken into account. In addition to the accounting and market-based performance measures that were employed in previous studies, South African companies' risk-adjusted performance was also taken into account. The capital asset pricing model and the Fama-French three-factor model were employed to estimate risk-adjusted abnormal returns for four corporate governance-sorted portfolios. Both estimations revealed that the portfolio comprising of companies with the highest corporate governance scores managed to significantly outperform the market.
Keywords: 650